APPLYING COGNITIVE LOAD THEORY IN TEACHING TENSES FOR SECOND LANGUAGE LEARNERS - Leni Amelia Suek (Englisia: Journal of Language, Education, and Humanities, 2018)
Cognitive load theory is a very useful concept that can be used by instructional designers, teachers, and educators to create effective instruction. It has been applied and developed in many areas including teaching English as a second or foreign language. In designing the instruction for teaching Tenses, worked example, split-attention effect, goal-free effect, modality effect, and redundancy effect are effective techniques that are used to reduce extraneous load, increase germane load, construct and automate schema. Designing and developing new instructions using cognitive load theory is also very useful. Teachers should understand this concept thoroughly because each instructional technique is connected to one another. In addition, it is very important to consider learners’ level of expertise, elements of interactivity and forms or sources of information before designing the instruction. Those elements of information and instructional techniques that are covered in the concept of cognitive load theory, should be well understood and applied by teachers particularly language teachers. Teaching foreign or second language is a big challenge for non-native English teachers; hence, effective instructional design can assist and enhance teaching learning process. This theory will contribute to positive outcomes where students understand the concept of Tenses thoroughly and teachers develop their teaching skill.